Rocket the brave - Hills, Tad (Schwartz & Wade Books, 2018)
Rocket the dog has fun chasing a butterfly up a hill and around a pond, but he does not want to follow it into the scary forest.
Keywords: Courage -- Fiction; Butterflies -- Fiction; Dogs -- Fiction